(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Different pedicle patterns have been used including superior, superomedial and medial pedicle techniques. A thin horizontal septum had been identified by Wuringer et al. which arises from the pectoral fascia at 5th rib. This septum divides the breast into cranial and caudal parts. It carries intercostal perforators and the main nerve supply to the NAC. Method: 20 patients are included in this study with septum-based superomedial breast reduction with mean distance for nipple transfer is 11.5 cm & 11.48 cm for right and left breast and mean excised breast tissue 930 gm & 894 gm for right and left breast respectively. Result: Complications occurred in 5 patients; hematoma in 2 patients, wound breakdown in 2 patients and partial nipple and areola necrosis in 1 patient. Conclusion: Combination of the horizontal breast septum with the superomedial pedicle in breast reduction surgeries allows for resection of the desired breast tissue while maintaining a good vascular supply to the nipple-areola complex with a minimal rate of complication.